Momentum and contrarian strategies in the Portuguese stock market - Pereira, Pedro Filipe Silveira Inácio Rodrigues (2010)
This thesis studies whether momentum and contrarian strategies are profitable on the Portuguese stock market and whether it is possible to obtain higher returns based on past performance trends. The time period analyzed is 1997-2008. The momentum strategy is based on the under-reaction hypothesis. This suggests that stocks that have had the best (worst) results in the recent past will continue to have better (worse) results in the near future, and therefore a trading strategy that buys winner stocks and sells the losers would provide significant abnormal returns. On the other hand, the contrarian strategy is based on the overreaction hypothesis which assumes the opposite behaviour from stock returns, and hence recommends buying losers and selling winners. Short term strategies show momentum profitability, thus supporting the under-reaction hypothesis. For longer periods, contrarian profitability (and overreaction) is also considerable but not so evident. An “innovative” investment strategy was developed that provides much higher returns than momentum and contrarian strategies. It is based on two upward past trends: if the past returns for the two defined periods preceding the holding period were equal or higher than the percentages defined, this stock is bought; otherwise, a safer investment such as a deposit with a risk-free rate is preferable. Results are not statistically significant but are economically relevant. Finally, results are robust to changes in the time-period, number of stocks included in the portfolios and after considering transaction and custody costs.